2021
DOI: 10.3390/microorganisms9091988
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Biocontrol Using Plant Growth-Promoting Bacteria (PGPR): Role of Bacterial Diversity

Abstract: A vast microbial community inhabits in the rhizosphere, among which, specialized bacteria known as Plant Growth-Promoting Rhizobacteria (PGPR) confer benefits to host plants including growth promotion and disease suppression. PGPR taxa vary in the ways whereby they curtail the negative effects of invading plant pathogens. However, a cumulative or synergistic effect does not always ensue when a bacterial consortium is used. In this review, we reassess the disease-suppressive mechanisms of PGPR and present expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 162 publications
0
50
0
Order By: Relevance
“…Hence, foliar treatment is more logical for infected plants ( Chandrashekar et al, 2018 ). The PR-1 and PR-5 gene expression are regulated by salicylic acid (SA), which is the primary mediator of the systemic acquired resistance (SAR) mechanism ( Breen et al, 2017 ; Wang et al, 2021 ). Thus, the results showed that 33504-Alex1 could boost SA-mediated SAR in faba bean when infected with BYMV.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, foliar treatment is more logical for infected plants ( Chandrashekar et al, 2018 ). The PR-1 and PR-5 gene expression are regulated by salicylic acid (SA), which is the primary mediator of the systemic acquired resistance (SAR) mechanism ( Breen et al, 2017 ; Wang et al, 2021 ). Thus, the results showed that 33504-Alex1 could boost SA-mediated SAR in faba bean when infected with BYMV.…”
Section: Discussionmentioning
confidence: 99%
“…Stenotrophomonas rhizophila strain SR80 enhanced wheat growth, both below and above ground, and induced strong disease resistance by boosting plant defence in the above-ground plant parts when the pathogen Fusarium pseudograminearum was present [148]. But there are several strains described with beneficial effects proved in cereals, such as wheat, rye or rice, as well as in other cultures such as barley, tomato, cucumber, pepper or Chinese cabbage (see reviews [43,72,149,150]). Organic amendments can also be supplemented with PGPB, and their effects on plants extended even further when compared to controls.…”
Section: Sustainable Agroecosystems and The Use Of Inoculant Microorg...mentioning
confidence: 99%
“…In phenazine-producing Pseudomonas, this quorum-sensing mechanism is well understood. Plant growth secreted toxin surface chemicals (bio-surfactants) and volatiles, chitinase cell wall-degrading enzymes, and -1,3glucanase enhancing rhizobacteria to reduce soil-borne pathogens [154][155][156]. The release of siderophore ligands, which efficiently grab iron and inhibit pathogen development, was previously identified as a biocontrol mechanism [157,158].…”
Section: Mechanism Of Antagonistic Bacteriamentioning
confidence: 99%